STUDI NARATIF DALAM FOTOGRAFI CERITA KEHIDUPAN JOHN KEI - Fransiskus Xaverius Chrisendi Wemaf; Silviana Amanda Tahalea (Jurnal Dimensi DKV Seni Rupa dan Desain, 2021)
AbstractNarrative Study of John Kei’s Life Story Photography. John Refra is a man coming from Southeast Maluku. The word “Kei” in his nickname came from his hometown name, which is Kei Island in Southeast Maluku. He was born on September 10th, 1969. In 1990, he moved to the capital city of Jakarta. From then, he started his new life and career. To complete this final paper, researcher tries to make another side of John Kei’s life into story photography. Story photography is an approach of telling a story using some photos and additional text to elaborate the context or the background. The aim of this paper is to promote John Kei’s personal life story and environment in a form of story photography which is expected to become a learning material for general society because it tells people that to be a better human being is not an easy thing to do. Researcher uses the literature review, observation, and interview method. The objects of this research are John Kei’s activities (6 photos) and the togetherness of John Kei with his family (3 photos). The photography technique used in this research is the narrative story photography technique which is aimed to lead the readers to follow the photo’s plot made by the researcher. As for the photo method, researcher uses the black and white photo. The result of this final paper is the description of facts and data about John Kei, his environment depiction, daily activities, and dressing style. Keywords: John Kei, narative study, story photography AbstrakStudi Naratif Dalam Fotografi Cerita Kehidupan John Kei. John Refra adalah pria asal Maluku Tenggara. Kata “Kei” di belakang panggilannya merujuk pada kampung kelahirannya, yaitu di Pulau Kei, Maluku Tenggara. John Refra lahir pada tanggal 10 September 1969. Pada tahun 1990, John Kei merantau ke ibu kota Jakarta. Dari situ dimulainya kehidupan seorang John Kei. Dalam perancangan Tugas Akhir ini, dibuat karya sisi lain kehidupan John Kei dalam fotografi cerita. Fotografi cerita adalah pendekatan bercerita dengan menggunakan beberapa foto dan tambahan teks untuk menjelaskan konteks atau latar belakang. Tujuan dari karya ini adalah mengangkat kisah kehidupan pribadi John Kei dan lingkungannya dalam bentuk  foto cerita, yang diharapkan dapat dijadikan sebagai pembelajaran bagi masyarakat pada umumnya bahwa proses berubah menjadi manusia yang lebih baik tidak mudah. Metode yang digunakan dalam membuat karya ini adalah studi pustaka, observasi, dan wawancara dengan narasumber. Objek dalam karya foto ini adalah aktivitas John Kei sebanyak 6 foto dan kebersamaan John Kei dengan keluarganya sebanyak 3 foto. Teknik foto yang digunakan adalah teknik fotografi cerita naratif dengan tujuan menggiring pembaca untuk mengikuti alur foto yang dibuat. Metode foto yang digunakan adalah foto hitam putih. Hasil dari karya tugas akhir ini adalah mendeskripsikan data dan fakta mengenai John Kei, gambaran lingkungan, kegiatan sehari-hari, dan termasuk berpakaiannya.Kata kunci: John Kei, studi naratif, fotografi cerita